Modern Types of Tests and Testing system in Uzbekistan - Bokiyeva , Mukaddas (International Journal of Psychosocial Rehabilitation, 2020)
This article categorizes language tests according to their purpose, function and important distinguishing characteristics as well as demonstrates the representative samples of each kind of test processes in Uzbekistan.